Exfoliated MXene as a mediator for efficient laser desorption/ionization mass spectrometry analysis of various analytes - Chae, Ari; Jang, Hongje; Koh, Dong-Yeun; Yang, Cheol-Min; Kim, Young-Kwan (ELSEVIER, 2020)
The exfoliated MXene (e-MXene) is systematically investigated as a mediator for laser desorption/ionization time-of-flight mass spectrometry (LDI-MS) analysis. Whereas un-exfoliated MXene has no activity for LDI-MS analysis, the e-MXene presents a high resolution, salt-tolerance and efficiency for LDI-MS analysis of various small molecules regardless of their polarity, aromaticity and molecular weight owing to its physicochemical properties such as high laser energy absorption, electrical conductivity and photothermal conversion. Based on our findings, it is clearly confirmed that e-MXene is a promising material for the development of an efficient platform for LDI-MS analysis of small molecules.
Keywords: SMALL MOLECULES; GRAPHENE OXIDE; MATRIX; DESORPTION; NANOSHEETS; OXIDATION; CARBON